“You walk within your outside limit on the outside”. Jurisdictional conflicts and territorial lack of control in Los Glaciares and Perito Moreno National Parks (Argentina) (Huellas, 2023)
Los Glaciares and Perito Francisco Pascasio Moreno National Parks are spaces with a strong regulatory system and nature in dispute. Taking this into account, this article analyzes the different laws and decrees that regulate the production of its limits, the conflicts between the National Parks and the province of Santa Cruz administrations, and the consequences for the development of activities by other land agents. Firstly, documentation was reviewed and, then, interviews and observation were conducted in each park. The obtained results allowed to indicate that the territorial lack of control resulting from normative ambiguity has diminished the exercise of institutional power and enabled the advancement of commercial frontiers typical of neoliberal conservation, primarily in Los Glaciares National Park.
Keywords: National Parks Administration; neoliberal conservation; commercial frontiers; licensed companies; land grabbing